2018
DOI: 10.1177/1755088218758117
|View full text |Cite
|
Sign up to set email alerts
|

The ethics of Carr and Wendt: Fairness and peace

Abstract: The, classical realist writings of E.H. Carr and constructivist publications of Alexander Wendt are extraordinarily influential. While they have provoked a great number of reactions within the discipline of International Relations, the ethical dimensions of their works have rarely been studied at length. This article seeks to remedy this lack of examination by engaging in an in-depth scrutiny of the moral concerns of these two mainstream International Relations scholars. On investigation, it is revealed that C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Arash Pashakhanlou’s recent response to charges of relativism can be situated in this pragmatist reading of Carr’s ethics. Contra relativist charges, Pashakhanlou argues that ‘fairness, defined as a judgment free from self-interest and deception in which the relevant parties are treated in an acceptable way under the given situation, is the ethical concern of Pashakhanlou (2018: 2). Carr’s concern with fairness and deception can be seen in his redefinition of the concept of peace.…”
Section: Carr Morality and The Crisis Of Laissez Fairementioning
confidence: 99%
See 2 more Smart Citations
“…Arash Pashakhanlou’s recent response to charges of relativism can be situated in this pragmatist reading of Carr’s ethics. Contra relativist charges, Pashakhanlou argues that ‘fairness, defined as a judgment free from self-interest and deception in which the relevant parties are treated in an acceptable way under the given situation, is the ethical concern of Pashakhanlou (2018: 2). Carr’s concern with fairness and deception can be seen in his redefinition of the concept of peace.…”
Section: Carr Morality and The Crisis Of Laissez Fairementioning
confidence: 99%
“…Miller (2016) recently concluded that ‘global political theory would benefit from a dose of realism’ (2016: 229). More recently, Pashakhanlou (2018) noted that ‘Carr’s concern with fairness overlaps with the interests of Rawlsians in International Relations (IR) and the conception of justice as fairness’ (2018: 12). To the extent that Carr was concerned with the individual and fairness respectively, this article concurs that there is an affinity between his ethics on the one hand, and cosmopolitans and Rawlsians on the other.…”
Section: Debating Global Justice With Carrmentioning
confidence: 99%
See 1 more Smart Citation